Discrimination in Evaluation: A Call for Greater Attention to Issues of Racial Discrimination in Experimental Musical Performance Evaluation Research - Cayenna Ponchione-Bailey (Music & Science)
This article provides a summary and critical review of the experimental perceptual studies within music psychology which have investigated the effect of evaluators’ perceived race of performers and the interaction with evaluators’ race on performance evaluations. With racial inequities continuing to be a major issue within historically-European classical music performance, controlled experimental studies can provide an important source of empirical data on which to base productive interventions. This article identifies a number of issues in the existing research which could benefit from future interdisciplinary collaboration. These include the need to define and control for racialized characteristics of performance variables, the need for further consideration of potential racial bias in evaluative frameworks and concepts, the need to address the racialization of research subjects and participants, and the need to avoid reaffirming harmful stereotypes through study designs and unsupported conjectures.